Kuzey Iraktaki Küçük Zap Suyunun Tagtag Bölgesinden Elde Edilen Sazan Balığı (Cyprinus carpio L., 1758) Boy-Ağırlik İlişkisi - Rashıd, Rzgar Farooq; Çalta, Metin; Başusta, Asiye (Fırat University, 2018)
Bu çalışmada, Kuzey Iraktaki Küçük Zap Nehrinin Tagtag bölgesinden elde edilen sazan (Cyprinus carpio L., 1758)’in toplam boy-ağırlık ilişkisi (LWR) incelendi. Bu amaçla, toplam olarak 100 adet sazan (56 dişi ve 44 erkek) kullanıldı. Balıkların toplam boy ve ağırlıkları ölçüldü. Toplam boyları 40-52 cm, ağırlıkları ise 1300-2620 g arasındadır. Toplam boy-ağırlık ilişkisinin logaritmik doğrusal denklemleri tüm bireyleri için LogW = - 1.007+2.574LogTL (r²=0.939), dişiler için LogW = -0.971+2553LogTL (r²=0.925) ve erkekler için ise LogW = - 1.61+2.607LogTL (r²=0.958) olarak bulundu. Tüm bireyler (), dişiler () ve erkekler () için hesaplanan “b” değerleri 3’den daha küçük bulundu. “b” değerlerine göre, Kuzey Iraktaki Küçük Zap Nehrinin Tagtag bölgesinde yaşayan sazan populasyonunun negatif allometrik bir büyüme gösterdiği görülmektedir.

In this study, total length-weight relationship (LWR) of common carp (Cyprinus carpio L., 1758) from Taqtaq Region of Little Zab River, Northern Iraq were determined. For this purpose, totally 100 carps (56 female and 44 male) were used. Total lengths and weights of them were measured. The total length and weight ranges were 40-52 cm and 1300-2620 g, respectively. The logarithmic and linear equations for total length-weight relationships (LWRs) were found as LogW = -1.007+2.574LogTL (r²=0.939) for combined sexes, LogW = -0.971+2553LogTL (r²=0.925) for females and LogW = -1.61+2.607LogTL (r²=0.958) for males. The “b” values calculated for combined sexes (2.574), for females (2.553) and for males (2.607) were smaller than 3. According to “b” values, common carp population living in the Taqtaq Region of the Little Zab River of Northern Iraq shows a negative allometric growth.
Length-Weight Relationship of Common Carp (Cyprinus carpio L., 1758) from Taqtaq Region of Little Zab River, Northern Iraq
Keywords: Engineering; Mühendislik